Metastasis-associated in colon cancer-1 and aldehyde dehydrogenase 1 are metastatic and prognostic biomarker for non-small cell lung cancer. Issue 1 (December 2016) - Zhou, Lei; Yu, Lan; Zhu, Bo; Wu, Shiwu; Song, Wenqing; Gong, Xiaomeng; Wang, Danna
Abstract Background Tumor recurrence and metastasis are the most common reason for treatment failure. Metastasis-associate in colon cancer-1 (MACC1) has been identified as a metastatic and prognostic biomarker for colorectal cancer and other solid tumors. Aldehyde dehydrogenase 1 (ALDH1), a marker of cancer stem cells, is also associated with metastasis and poor prognosis in many tumors. However, the prognostic value of either MACC1 or ALDH1 in non-small cell lung cancer (NSCLC) is unclear. In this study, we explored the relationship between MACC1 and ALDH1 expression, as well as their respective associations with clinicopathological features, to determine if either could be useful for improvement of survival prognosis in NSCLC. Methods The expression levels of both MACC1 and ALDH1 in 240 whole tissue sections of NSCLC were examined by immunohistochemistry. Clinical data were also collected. Results MACC1 and ALDH1 were significantly overexpressed in NSCLC tissues when compared to levels in normal lung tissues. Investigation of associations between MACC1 or ALDH1 protein levels with clinicopathological parameters of NSCLC revealed correlations between the expression of each with tumor grade, lymph node metastasis, and tumor node metastasis. The overall survival of patients with MACC1- or ALDH1-positive NSCLC tumors was significantly lower than that of those who were negative. Importantly, multivariate analysis suggested that positive expression of either MACC1 or ALDH1, as well as TNM stage, could be independent prognostic factors for overall survival in patients with NSCLC. Conclusions MACC1 and ALDH1 may represent promising metastatic and prognostic biomarkers, as well as potential therapeutic targets, for NSCLC.